2011
DOI: 10.1523/jneurosci.4141-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Early Maturation of the Linguistic Dorsal Pathway in Human Infants

Abstract: Human infants, unlike even closely related primates, exhibit a remarkable capacity for language learning. Yet how the underlying anatomical network matures remains largely unknown. The classical view is that of a largely immature brain comprising only a few islands of maturity in primary cortices. This view has favored a description of learning based on bottom-up algorithms and has tended to discard the role of frontal regions, which were assumed to be barely functional early on. Here, using an index based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
116
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(121 citation statements)
references
References 38 publications
4
116
0
1
Order By: Relevance
“…Gene expression in the inferior frontal regions is more similar to other temporal and parietal speech areas than to other frontal areas (37). Leroy et al (34) observed a correlation in the maturation of the inferior frontal region (area 44), the posterior temporal region, and the arcuate fasciculus during the first weeks of life. These results suggest that the superior temporal, inferior parietal, and inferior frontal regions, although distributed across three lobes, belong to a single functional unit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gene expression in the inferior frontal regions is more similar to other temporal and parietal speech areas than to other frontal areas (37). Leroy et al (34) observed a correlation in the maturation of the inferior frontal region (area 44), the posterior temporal region, and the arcuate fasciculus during the first weeks of life. These results suggest that the superior temporal, inferior parietal, and inferior frontal regions, although distributed across three lobes, belong to a single functional unit.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier research already established that the left inferior frontal region, one of the key regions of the adult linguistic network, is already active during speech perception in postterm infants (3,34). However, it was suggested that its involvement might be secondary to infant's first vocal productions (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…TFs are proteins that regulate the expression levels of their target genes through binding to specific DNA sequence motifs that are located in the vicinity of their target genes in the genome (9,11). We used binding motif data for each of 615 motifs to define sets of TF target genes.…”
Section: Tf Target Genesmentioning
confidence: 99%
“…Left-right anatomical differences of the cerebral hemispheres have been detected by ultrasound scanning as early as 18 weeks postconception (8). In infants, the right hemisphere has been reported to develop functionally and anatomically earlier than the left hemisphere in various respects, including that left hemisphere language-related brain regions develop more slowly than their contralateral counterparts (9)(10)(11). These observations indicate a broadly lateralized program of motor and cognitive development that begins in utero in our species and suggest that a general model can involve different rates of maturation on the two sides of the central nervous system (CNS).…”
mentioning
confidence: 99%
“…The picture is clearer in newborns, where leftward asymmetry of the arcuate fasciculus has been observed at birth (Dubois et al 2009;Leroy et al 2011). Thus, even if hemispheric dominance corresponds to differences in cognitive processes, the structure of the two hemispheres follows the same anatomo-functional organizational rules.…”
Section: Intra-hemispheric Structural Connectivitymentioning
confidence: 98%